Aeration systems and stocking densities on water quality and production of Nile tilapia (Research, Society and Development, 2021)
Aiming to evaluate the water quality and performance of tilapia in different aeration systems and stocking densities, an experiment was conducted in a completely randomized design, in a 3x3 factorial (three aeration systems: no aeration; radial compressor aerator; fountain aerator) and three stocking densities: (3, 6 and 9 fish/m3). The experiment was carried out for 252 days, using reversed fingerlings (weight 16.3 g) and rationed with diets containing 29.5% crude protein. The fish were considered as the experimental unit for final mean body weight (PCF), daily weight gain (GPMD) and the tank for biomass production (PBI), apparent feed conversion (CAA) and limnological variables. Differences were observed for oxygen, ammonia and orthophosphate. Aerations and densities influenced the averages of oxygen in the water. Ammonia was influenced only by density. The PBI (D1 = 1.29, D2 = 1.91 and D3 = 2.44 kg/m3) increased with the increases in density, however, it reduced the PCF, GPMD. CAA was not different between treatments. The highest PCF (512.9 g) and GPMD (1.83 g/day) was at the density of 3 fish/m3, while the highest GNP was observed at the density of 9 fish/m3 (2.44 kg/m3). There is no need for aeration at the lowest density; for the intermediate, the radial compressor was more efficient, while for 9 fish/m3, the aeration systems had similar effects. With the interaction of the two variables (density and aeration), the most suitable density is 6 fish/m3, with aeration by radial compressor.